DE-GENERATIES : Elias et ses compagnons de routes : 80 artistes. - Elias, Willem; Vanderstichelen, Sven (Brussel : De Markten, 2016)
Benhelima, Charif ; Bervoets, Fred ; Bilquin, Jean ; Bogart, Bram ; Bolenz, Ulrike ; Braet, Hilde ; Burssens, Jan ; Buylen, Michel ; Chiafele, Erik ; Clarysse, Johan ; Cloet, Mark ; D'havé, Camille ; De Buck, Siegfried ; De Clerq, Hugo ; De Cupere, Peter ; De Kramer, Enk ; De Meester, Karel ; De Smedt, Jo ; De Vliegher, Jan ; Deconynck, Jan ; Desmet, Etienne ; Dierickx, Karel ; Dillemans, Sam ; Duchateau, Hugo ; Dimma, Etiyé ; Everaert, Hans ; Fillet, Steven ; Hoenraet, Luc ; 't Kindt, Jacques ; Lambrechts, Marc ; Laperre, Lode ; Leclercq, Guy ; Ledent, Ingrid ; Maieu, Frank ; Mannaers, Werner ; Marcase ; MarieAnge ; Mary, Anthony ; Michielsen, Bart ; Mugo ; Naudts, Filip ; Nollet, Lieven ; Reniere en Depla ; Roobjee, Pjeroo ; Van Nuffel, Seraphine ; Slangen, Nancy ; Spie, Merlin ; Stockmans, Piet ; Tahon, Johan ; Van Autgaerden, Greet ; Van Breedam, Camiel ; Van de Vyvere, Ann ; van den Abbeel, Jan ; Van den Berghe, Roland ; Van Den Broek, Koen ; Van Den Dorpe, Willy ; Van Gestel, Fik ; Van Gysegem, Paul ; van Herreweghen, Anne ; Van Imschoot, Jan ; Van Oost, Jan ; Van Praet, Frans ; Van Schuylenbergh, André ; Van Simaey, Frederik ; van Stapele, Nicoline ; Vanden Eynde, Maarten ; Vandenberg, Philippe ; Vander Eecken, Dirk ; Vandevelde, Juul ; Vandevijvere, Bart ; Velter, Yves ; Verdegem, Jos ; Vertessen, Liliane ; Vlerick, Pierre ; Waeghe, Colin ; Waterschoot, Peter ; Weidenbaum, Peter ; Woestenborghs, Tom ; Wyckaert, Maurice
DE-GENERATIES : Elias et ses compagnons de routes : 80 artistes, De Markten, Brussel, 10/11/2016 - 11/12/2016
boek